Management of Through-and-Through Oromandibular Defects after Segmental Mandibulectomy with Fibula Osteocutaneous Flap - Mathews, Saumya; Jaiswal, Dushyant; Yadav, Prabha; Shankhdhar, Vinay Kant; Hadgaonkar, Sumit; Mantri, Mayur; Bindu, Ameya; Pilania, Vineet; Mohammad, Arbab; Escandón, Joseph M. (Journal of Reconstructive Microsurgery, 2023)
Background Oromandibular defects involving the external skin are a reconstructive challenge. This study aimed to evaluate the use of the fibula osteocutaneous free flap (FOCFF) for through-and-through oromandibular defects by comparing the surgical outcomes and complications of different techniques to close the external skin defect.Methods A retrospective analysis was conducted of patients who underwent reconstruction of through-and-through oromandibular defects after oncologic segmental mandibulectomy between January 2011 and December 2014. Five groups were analyzed according to the method of external skin coverage: primary closure, locoregional flaps, deepithelialized double-skin paddle FOCFF (deEpi-FOCFF), division of the skin paddle for double-skin paddle FOCFF (div-FOCFF), and a simultaneous second free flap. Intraoperative and postoperative outcomes along with complications were analyzed between groups.Results A total of 323 patients were included. The mean total defect area requiring a simultaneous second free flap was larger in comparison to other groups (p < 0.001). Reconstructions performed with div-FOCFF had a higher number of perforators per flap when compared with deEpi-FOCFF (p < 0.001). External defects closed with another free flap exhibited higher intraoperative time for the reconstructive segment in comparison to other groups (p < 0.05). The overall rate of complications was comparable between groups (24%, p = 0.129).Conclusion The FFOCF is a reliable alternative to harvesting multiple simultaneous free flaps for through-and-through oromandibular defects. The authors recommend appropriate curation of the surgical plan based on individual patient characteristics and reconstructive requirements.
Keywords: fibula; head and neck neoplasms; reconstructive surgical procedures; postoperative complications; surgical flaps